PERAN GURU PAI DALAM MENINGKATKAN KUALITAS AKHLAK MENGAJAR PERSPEKTIF AL-QUR'AN DI SMP NEGERI 4 PERANAP - Muhartini, Muhartini; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
PAI teachers not only teach expected field changes in education, but rather inculcate noble character, noble character education is the main concern of Islamic education because faith in Allah is seen and manifested in noble character. The Role of PAI Teachers in Improving the Quality of Teaching Morals from the Perspective of the Qur'an includes; giving an example of arriving on time, carrying out class rules, paying attention to each student, being assertive in teaching, guiding students to carry out worship, asking to collect assignments on time, and providing encouragement to study motivation. This research method is cross-sectional conducted at SMP Negeri 4 Peranap. The results of this study are seen from all 7 statements, it can be seen that 78% of teachers try to improve the moral quality of students through various concrete examples, 19% rarely and 3% never. The efforts of teachers who are always at the forefront of educational institutions are a separate motivation and driver for students to always be role models by improving the quality of teaching morals from the perspective of the Qur'an